Two new species of Gaeolaelaps Evans & Till (Acari: Laelapidae) from Sri Lanka - Joharchi, Omid; Khaustov, Alexander A.; Ermilov, Sergey G. (Zootaxa, 2019)
Two new mite species of the genus Gaeolaelaps (Laelapidae), G. lankaensis sp. nov. and G. setillus sp. nov., collected from soil-litter in Sri Lanka, are described and illustrated based on morphological characters of the adult females. Both species have the unusual character state of a three-tined palp tarsal claw. The genus Gaeolaelaps is reported for the first time from Sri Lanka. An updated key to the species with a three-tined palp tarsal claw is presented.